2014
DOI: 10.4049/jimmunol.1400210
|View full text |Cite
|
Sign up to set email alerts
|

Negative Self-Regulation of TLR9 Signaling by Its N-Terminal Proteolytic Cleavage Product

Abstract: TLR signaling is essential to innate immunity against microbial invaders and must be tightly controlled. We have previously shown that TLR9 undergoes proteolytic cleavage processing by lysosomal proteases to generate two distinct fragments. The C-terminal cleavage product plays a critical role in activating TLR9 signaling; however, the precise role of the N-terminal fragment, which remains in lysosomes, in the TLR9 response is still unclear. In this article, we report that the N-terminal cleavage product negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…This proteolytic event generates a soluble form of the receptor that is capable of binding CpG DNA and inhibiting signaling through the full-length receptor. Additionally, when TLR9 1-440 was fused to a transmembrane domain, it acted as a dominant negative inhibitor of signaling (27). Thus, we next investigated whether the N-terminal fragment, without a transmembrane domain, could associate with full-length TLR9 and negatively regulate TLR9 signaling.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This proteolytic event generates a soluble form of the receptor that is capable of binding CpG DNA and inhibiting signaling through the full-length receptor. Additionally, when TLR9 1-440 was fused to a transmembrane domain, it acted as a dominant negative inhibitor of signaling (27). Thus, we next investigated whether the N-terminal fragment, without a transmembrane domain, could associate with full-length TLR9 and negatively regulate TLR9 signaling.…”
Section: Resultsmentioning
confidence: 99%
“…Thus it is interesting that two different studies obtained conflicting results regarding the function of the N-terminal fragment. Onji et al suggest it is required for signaling (32), while Lee et al suggested that the N-terminal fragment associates with full-length TLR9 and is a negative regulator (27). We have observed that our soluble TLR9 proteolytic fragment can be additionally cleaved to generate the same N-terminal fragment (data not shown and (26)).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its participation in ligand binding, the N‐terminal fragment of TLR9 might have an additional regulatory role . Lee et al .…”
Section: Proteolytic Processing Of the Extracellular Lrrsmentioning
confidence: 99%
“…In addition to its participation in ligand binding, the N-terminal fragment of TLR9 might have an additional regulatory role (80). Lee et al (80) fused the N-terminal fragment of TLR9 to its transmembrane domain and a cytosolic green fluorescent protein (GFP) in order to target the N-terminal part of TLR9 into the physiologically relevant compartment. Using this construct, the authors found that the presence of the N-terminal fragment induced pepstatin A-sensitive degradation of the C-terminal fragment.…”
Section: Cleavage Of Tlr9mentioning
confidence: 99%